The effects of intermitentt contract on the domestic work as encouragement of underemployment and informality (Research, Society and Development, 2019)
The present article seeks to present the possible effects of Law 13.467/17 as incentives to informality and the devaluation in relation to domestic employment, demonstrating how the flexibilization of rights and the new contractual figures represent a greater precariousness to domestic service, especially through its social and legal characteristics. In the Brazilian scenario, the devaluation and the employer's refusal to comply with labor charges are the causes behind the great informality, which worsened in the face of the economic crisis. We use, therefore, the deductive method and the bibliographical and documentary research technique to observe the inadequacy of the reform in the search for modernization of the labor market, as it has broken down the working hours and stimulated the low remuneration and stability of employment, while long working hours are still demanded by the employer in the Brazilian reality, which will result in an increase in the informal environment for domestic service, representing, that way, the reform as a contribution to the precarious state of the Brazilian social right.